Longman Dictionary of Contemporary English. New Edition - Mayor, Michael (Harlow Pearson Education Limited, 2009)
The Longman Dictionary of Contemporary English (LDOCE) ia brilliant both at capturing such relations between words and at presenting them to the learner on an attractive and instantly comprehensible way that makes them easily memorable. In this current edition, Collocation boxes present users with over 65,000 common collocations whilst the integrated Thesaurus explains the differences between some 18,000 synonyms and closely related words. All of this information is illustrated with examples taken from the Longman Corpus Network.
Keywords: English Practice